PENGARUH PROFESIONALISME GURU DAN PENGEMBANGAN KEPROFESIAN BERKELANJUTAN TERHADAP MUTU PENDIDIKAN MELALUI KUALITAS GURU SEBAGAI VARIABEL INTERVENING DI MADRASAH IBTIDAIYAH NEGERI KABUPATEN TANGERANG - Agustina; Ahmad Mukhlis; Angrian Permana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The quality of education has received increasing attention in recent years, along with the awareness of policy makers and stakeholders of the importance of education in driving economic and social development. The purpose of the study conducted at the State Elementary School of Tangerang Regency, to analyze the Influence of Teacher Professionalism and Continuing Professional Development on the Quality of Education through Teacher Quality as an Intervening Variable. The analysis method in this study uses descriptive index numbers and SEM PLS as inferential analysis. The study was conducted on 7 Madrasah Ibtidaiyah in Tangerang Regency which focused on 144 honorary teachers with the determination of the number of samples proportionally with a percentage. The results of the study showed that 5 hypotheses were accepted while 2 hypotheses were rejected. The conclusion of this study is that the 2 exogenous variables are good predictors for predicting education quality, while continuous professional development is unable to predict education quality.